Efektivitas Media Game dalam Meningkatkan Keterampilan Berpikir Kritis Siswa pada Mata Pelajaran Pendidikan Agama Islam - Laila Laila; Rusmiati Indrayani; Satriah Satriah (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the effectiveness of game media in improving students’ critical thinking skills in Islamic Religious Education subjects at SMPN 5 Sangatta Utara. This research employed a classroom action research (CAR) method conducted through several cycles to improve the learning process and enhance students’ critical thinking abilities. The implementation of game media in Islamic Religious Education learning had a positive impact by increasing students’ involvement, motivation, and active participation during learning activities. Before the implementation of the action, pre-cycle data were collected based on students’ learning outcomes in the material of believing in the books of Allah SWT. The results showed that students’ learning completeness reached 67%, which was still below the Minimum Completeness Criteria (KKM). After implementing game media in cycle I, students’ learning completeness increased to 76%, indicating improvement but still requiring further action. In cycle II, improvements were made through the continued application of game media, resulting in a significant increase in students’ learning completeness to 100%. These findings indicate that game media is effective in improving students’ critical thinking skills and learning outcomes in Islamic Religious Education. Therefore, the use of interactive learning media can be an alternative strategy to create an engaging learning environment and support students’ academic achievement.